Development of an automated positioning system for dosimetry in teletherapy (Research, Society and Development, 2023)
Radiotherapy can be divided into two modalities: brachytherapy and teletherapy, the latter being the most widespread technique. Teletherapy equipment is capable of producing beams of photons or electrons that leave the equipment towards the patient positioned on the treatment table. To ensure that the irradiation field provides the correct dose and that the beams produced focus only on the region of interest, it is necessary to carry out a series of quality control tests, with part of these tests carried out using specific dosimetry equipment. : a dosimetric set, in addition to a simulator (phantom) filled with water that simulates the interaction of the beam with the human body. Depending on the amount of energy that the linear accelerator can produce, and considering that quality control must be carried out periodically on each of the energies available in the equipment, the entire process ends up becoming too slow and time-consuming, when using a simulator. manual activation compared to automated equipment. The objective of this work was to design and build low-cost automated equipment, based on an open source platform (Arduino), with access to affordable parts comparable to devices dedicated to quality control in radiotherapy available on the market. And it is also expected, in future work, to develop software that, together with the equipment, is capable of carrying out the process of scanning the radiation beam. It is, therefore, research of an applied nature.